Synthesis and characterization of corrosion protective poly(2,5-dimethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Applied Surface Science, 2006)
Poly(2,5-dimethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of 2,5-dimethylaniline in aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly (2,5-dimethylaniline) coatings on Cu substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique. The results of the potentiodynamic polarization demonstrate that the poly(2,5-dimethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(2,5-dimethylaniline) coated Cu than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 5-dimethylaniline) coatings; conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Poly(2

Synthesis of MgNb2O6 by coprecipitation - Navale, S. C.; Gaikwad, A. B.; Ravi, V. (Materials Research Bulletin, 2006)
A simple coprecipitation technique was used successfully to synthesize fine powders of MgNb2O6 (MN) phase. An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Mg2+ and Nb5+ cations as carbonate and hydroxide respectively under basic conditions. This precipitate on heating at 750 degrees C produced MN powders. For comparison MN powders were prepared by the traditional solid state method. The phase content and the lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology of the particles were studied by scanning electron microscopy (SEM). (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction

Synthesis of star shaped Ba1-xSrTiO3 (BST) powders - Khollam, Y. B.; Potdar, H. S.; Deshpande, S. B.; Gaikwad, A. B. (Materials Chemistry and Physics, 2006)
Uniform star shaped strontium substituted barium titanyl oxalate Ba1-xSrxTiO(C2O4)(2) (BSTO)/strontium substituted barium titanate, Ba1-xSrxTiO3 (BST) powders were prepared via a simple chemical co-precipitation route with x = 0.15, 0.20, and 0.25. The process involved an addition of 0.1 M solution of titanium tetrabutoxide (BTM) in isopropanol (IPA) to 0.1 M oxalic acid in IPA containing 0.2 M of H2O to produce titanyl oxalate precipitate which was further reacted with 0.1 M solution of ammonium oxalate to obtain 0.1 M clear homogeneous solution of ammonium titanyl oxalate (ATO) with pH 4.25 containing titanium in the form of soluble anionic oxalate species [TiO(C2O4)(2)(2-)]. Stoichiometric quantities of barium hydroxide and strontium nitrate were dissolved in distilled water and its pH was adjusted nearly equal to that of ATO (similar to 4.15) by drop wise addition of dilute HNO3 solution 1:10 (v/v). The addition of this mixed cation precursor solution to ATO solution resulted in precipitation of strontium substituted barium titanyl oxalate (BSTO) having star shaped morphology. The calcination of BSTO precursors at 730 degrees C for 4 h in air produced cubic BST powders (a(o) similar to 4.001, 3.996 and 3.991 angstrom for x = 0. 15, 0.20, 0.25, respectively) having star shaped morphology. SEM, XRD and IFTIR techniques were used to characterize the BSTO/BST powders. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; capping agent; Co-precipitation; Morphology

Synthesis and corrosion protection study of poly(o-ethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Surface & Coatings Technology, 2008)
Poly(o-ethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-ethylaniline in an aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethylaniline to generate strongly adherent and smooth poly(o-ethylaniline) coatings on Cu substrates. The performance of poly(o-ethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies demonstrate that the poly(o-ethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(o-ethylanitine) coated Cu (similar to 15 mu m thick) than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 70. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings

Synthesis and corrosion protection aspects of poly(o-toluidine)/CdO nanoparticle composite coatings on mild steel - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Journal of Coatings Technology and Research, 2010)
This study examines the possibility of using poly(o-toluidine)/CdO (POT-CdO) nanoparticle composite coating for corrosion protection of mild steel in chloride environment. The POT-CdO nanoparticle composite coating was synthesized on mild steel from aqueous tartrate solution containing CdO-nanoparticles (size similar to 18 nm) by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-Visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction measurements. The corrosion protection aspects of the resulting POT-CdO nanocomposite structure were investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of these investigations reveal that the POT-CdO nanoparticle composite acts as a protective coating on mild steel and reduces the corrosion rate of mild steel almost by factor of 70.
Keywords: CdO; Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Mild steel; Nanocomposites; Poly(o-toluidine)

Structural and surface morphological properties of chemically deposited Mo0.5W0.5S2 thin film - Patil, A. A.; Hankare, P. P.; Gaikwad, A. B.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2012)
Preparation of layered type semiconductor Mo0.5W0.5S2- thin films has been successfully done by using chemical bath deposition method. Objective of the studies are related to structural, optical, morphological and electrical properties of the thin films. The preparation method is based on the reaction between tartarate complex of Mo and W with thiourea in an aqueous alkaline medium at 363 K. X-Ray diffraction reveals a polycrystalline film composed of both MoS2 and WS2 phases. The optical study shows that the band gap of the film is 1.6 eV. Electrical conductivity is high which is in the order of 10(-3)-10(-2) (Omega cm)(-1).